Effect of weld profile on the torsion performance of the components - Turaidas S Rajaraam (School of Mechatronics Engineering, Universiti Malaysia Perlis, 2009)
Welded joints are subjected to various forms of cyclic loading in practical applications and fatigue failure is common. In this research, an approach to study the weld influence of welded structure has been developed and specifically, the concept has been applied to butt-welded joint in a cylindrical model.